Oral pregabalin as preemptive analgesia and reduces the dose of diclofenac consumption during the postoperative period of gynaecological operation under spinal anaesthesia- a randomized, placebo-controlled study - Ratindra Kumar Barman; Hiranya Kumar Saharia; Ananta Hazarika; Karamchand Basumatary (Barpeta Obstetrics and Gynaecological Society, 2022)
Background: Majority of gynaecological surgeries are performed under spinal anaesthesia because of ease of technique and various side effects associated with general anaesthesia. Multimodal analgesia has been recommended nowadays for perioperative pain. Gabapentinoids are been increasingly being used as preemptive analgesia for postoperative pain management. Objectives: The purpose of this study was to assess if preoperative pregabalin had any effect on postoperative analgesic requirement in patients undergoing hysterectomy under spinal anaesthesia. Methods: It was a randomized, double-blind, placebo-controlled trial involving 80 women with ASA I and II who were undergoing gynaecological surgeries under spinal anaesthesia and were divided into two groups (n=40). One hour before anaesthesia, group P received pregabalin 75mg and group C received placebo, both in the form of identical gelatinous capsules. The visual analogue scale for postoperative pain, the Ramsay Sedation Scale for sedation, and postoperative nausea and vomiting (PONV) scale were all used in the study. Results: In group P, the number of patients with VAS ≥4 at 6, 24, and 48 hours was lower than in group C. At 12 hours, however, the number of patients with a VAS ≥ 4 was higher in group P than in group C. The cumulative diclofenac consumption in the pregabalin group was significantly reduced. Throughout the interval, group P had a slightly higher Ramsay sedation score than group C. PONV was greater in group P after surgery. Conclusion: Preoperative administration of 75 mg of pregabalin 1 hr before spinal anaesthesia resulted in a significant reduction of diclofenac consumption after major gynaecological surgeries.